Using Primer-ID Deep Sequencing to Detect Recent Human Immunodeficiency Virus Type 1 Infection. (16th July 2018) - Dennis, Ann M; Zhou, Shuntai; Sellers, Christopher J; Learner, Emily; Potempa, Marc; Cohen, Myron S; Miller, William C; Eron, Joseph J; Swanstrom, Ronald
Abstract : Primer-ID reduces HIV-1 sequencing error, a limitation of conventional next-generation sequencing (NGS). The distribution of pairwise genetic distances from Primer-ID NGS can be used to select thresholds to detect recent infection (<9 months) with high sensitivity and specificity, including in multivariant transmission. Abstract: Intrahost viral sequence diversity can be evaluated over multiple genomic regions using next-generation sequencing (NGS) and scaled to population-level diversity to identify recent human immunodeficiency virus type 1 infection. Using Primer-ID NGS, we sequenced the reverse transcriptase (RT) and env V1–V3 regions from persons with known infection dates, and assessed the mean (π) and first quintile of pairwise diversity distributions over time. The receiver operating characteristic area under the curve (AUC) of RT and V1–V3 combined showed excellent discrimination of recent infection <9 months: using π (only single transmitted variants: AUC, 0.98; threshold <1.03%; sensitivity, 97%; specificity, 89%) and the first quintile (including all variants: AUC, 0.90; threshold <0.60%; sensitivity, 91%; specificity, 92%).